Organizational learning with the implementation and maintenance of ISO 14001: an exploratory study in an autoparts company - Santos, Carlos Jonathan Da Silva; Matos, Juscely Reis (Revista de Administração da UFSM, 2016)
The aim of this study, considered exploratory, is to identify the learning on organizational level of an auto parts company with the implementation and maintenance of an Environmental Management System according to the rules of ISO 14001. It relies on the theoretical framework that focuses on organizational learning as a product or a process producing a product. To get an understanding of organizational learning was considered appropriate to interview two key people in the implementation and maintenance of ISO 14001. Their descriptions were hermeneutically interpreted by inductive analysis process and resulted in the understanding that the company studied had, in the process of implementation and maintenance of the ISO 14001, the generation of a product, that was organizational learning relating with the management of the environment.